(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
The establishment of private universities has become one of the means to spreading university education and expanding it in the Iraqi society within the framework of the university education strategy to expand education and this type of education is encouraged at the government level according to a philosophy that stems from the principle of integration between government education and private education and considering the latter is one of the complementary substitutions to public university education. One of the most important advantages of private university education is that it gives greater freedom to choose colleges and scientific specializations according to the desire of the students who are applying to study in private universities. The most important conclusions of the research are that private universities do not suffer from the problem of disguised unemployment sometimes as they often adopt flexible administrative structures that ensure high performance efficiency for all of their affiliates and on the contrary they take all necessary measures against persons whose performance does not rise to the required level in terms of administrative, and scientific levels. Among the most important recommendations of the research are the values of private colleges and universities to gain the confidence of the citizen so that it competes with public university education, promotes it, and encourages private education according to a philosophy that stems from the principle of integration between government education and private education.